Improving Students’ Achievement in Writing Descriptive Paragraph through Teaching Prewriting Stages - Puji Hariati (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2020)
This study was aimed to find out whether or not Teaching Prewriting Stages can improve students’ ability in writing descriptive paragraphs, to describe the role of prewriting stages in helping the students to write descriptive paragraphs. This study was conducted by using Classroom Action Research. It was done through 1) planning, 2) action, 3) observation, and 4) reflection. The population and the sample was the ninth grade students of SMP Swasta BUDISATRYA at 2018/2019 academic year. This research applied quantitative and qualitative method. Quantitative data were taken from the students' writing descriptive paragraph test. Qualitative data were taken from observation, interview, and diary notes. The result of the research shows that there was some improvement of students’ ability in writing descriptive paragraphs through teaching prewriting stages. It can be proved from the students' score which improved from cycle 1 to cycle 2.  The improvement can be seen that in pre test the means score was 33.52. In the first cycle, meeting 1 the means score was 37.35, in meeting 2 was 42.64 and in meeting 3 was 52.64. In the second cycle, meeting 1 the means score was 64,41,  in meeting 2 was 80 and in meeting 3 was 91.17. The improvement also can be seen from the percentage of the students’ achievement in writing descriptive paragraph by using prewriting stage; in pre test, no one of the students got 75 points. In the first cycle, in meeting 1, and meeting 2, there was also no one student got 75 point,  but in meeting 3 there was 23,52% (8 students) got 75 points. It means there was an improvement about 23.52 % . In the second cycle, in meeting 1 there was 29.41% (10 students) got 75 points, it means that there was an improvement about 5.89%. In meeting 2 there was 79.41% (27 students) got 75 points, it means that there was an improvement about 50%.  In meeting 3 there was 100% (34 students) got up 75 points. It means that prewriting stages helped the students to write descriptive paragraphs through brainstorming, listing supporting point, making a simple outline to write event, place or object related to the topic. So, the students’ achievement in writing descriptive paragraph is significantly improved by applying prewriting stage.